Surveillance and genetic characterization of Listeria monocytogenes in the food chain in Montenegro during the period 2014–2022 - Daza Prieto, Beatriz; Pietzka, Ariane; Martinovic, Aleksandra; Ruppitsch, Werner; Zuber Bogdanovic, Ivana (Frontiers in Microbiology, 2024)
Listeria monocytogenes is an ubiquitous foodborne pathogen that represents a serious threat to public health and the food industry. In this study Whole Genome Sequencing (WGS) was used to characterize 160 L. monocytogenes isolates obtained from 22,593 different food sources in Montenegro during the years 2014-2022. Isolates belonged to 21 different clonal complexes (CCs), 22 sequence types (STs) and 73 core genome multilocus sequence types (cgMLST) revealing a high diversity. The most prevalent STs were ST8 (n=29), ST9 (n=31), ST121 (n=19) and ST155 (n=20). All isolates carried virulence genes (VGs), 111 isolates carried mobile genetic elements (MGEs) (ranging from 1-7 MGEs) and 101 isolates carried plasmids (ranging from 1-3 plasmids). All isolates carried the intrinsic resistance genes fosX and lin. None of the isolates carried acquired antimicrobial resistance genes (ARGs).